Optimal Fiscal Policy with Labor Selection - Sanjay K. Chugh; Wolfgang Lechthaler; Christian Merkl (Institute of Labor Economics (IZA), 2018)
This paper characterizes long-run and short-run optimal fiscal policy in the labor selection framework. In a calibrated non-Ramsey decentralized equilibrium, labor market volatility is inefficient. Keeping fixed the structural parameters, the Ramsey government achieves efficient labor market volatility; doing so requires labor-income tax volatility that is orders of magnitude larger than the "tax-smoothing" results based on Walrasian labor markets, but a few times smaller than the results based on search and matching markets. We analytically characterize selection-model-consistent wedges and inefficiencies in order to understand optimal tax volatility.
Keywords: E24; E32; E50; E62; E63; J20; 330; labor market frictions; hiring costs; efficiency; optimal taxation; labor wedge; zero intertemporal distortions